Implementasi Kebijakan Pencegahan Penyalahgunaan Narkotika pada Anak - Ilham, Rianza Naufalfalah; Adhari, Ade (Universitas Muhammadiyah Ponorogo, 2025)
Drug abuse among children in Tangerang City is a serious problem that requires greater attention from various parties. This study aims to examine the implementation of drug abuse prevention policies for children in Tangerang City, as well as to identify obstacles and supporting factors in their implementation. The policies that have been implemented involve various sectors, including education, health, and law enforcement. Children, as individuals who are still in their developmental stage, require an approach that builds awareness and resilience, rather than one that stigmatizes them. Therefore, prevention policies need to be designed in such a way that they can reach children through age-appropriate education, safe and supportive environments, and the involvement of families and schools as the first line of defense in protecting children from the threat of drugs. Under Law No. 23 of 2002 on Child Protection, as amended by Law No. 35 of 2014 and most recently by Law No. 17 of 2016, Article 13(1) and (2) state that children have the right to protection from the abuse of narcotics, psychotropic substances, and other addictive substances. Additionally, Article 59(2)(d) mandates the state and government to provide special protection to children who are victims of drug abuse. However, evaluation results indicate challenges in inter-agency coordination, lack of active participation from parents and the community, and limited resources in implementing these policies. This study suggests the importance of a more integrated approach, involving the community actively, and strengthening the capacity of implementing institutions to achieve success in preventing drug abuse among children.